Modelado numérico del cartílago sinovial sujeto a deformación - Martínez Gutiérrez, Nancy (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
In this work, a numerical simulation was developed to model a synovial joint, from a mechanical point of view andit was analyzed as a bio-bearing. Most of the literature reviewed show mathematical models and it is only analyzed in the synovial fluid region. For this reason, a validation study of the synovial fluid region in contact with the bio-bearing is presented at the begining, this region show a deformation proportional to the induced displacement. Subsequently, ageometry with two regions was used in the numerical model for validation corresponding to the synovial fluid and the articular cartilage. The geometry was based on the mathematical study proposed by Jurczak [1], on that work the region for the synovial fluid has a induced deformation and the cartilage has a porosity of 0,2. Additionally to the results obtained, a new model is proposed in which the deformation takes place on the cartilage region, and it was able to work in a wider range of porosity values of 0,2, 0,5 and 0,8. The results were obtained for different values in displacement and velocities, in order to simulate different movements or situations that might appear in a real knee. The numerical model of the system was developed using Computational Fluid Dynamics (CFD) on Fluent®, where one of the most important tools used in the simulations was the dynamic mesh application. With this numerical tool, the movil wall has a displacement to simulate a deformation induced by a load through the femur bone besides to produce a dynamic remeshing in the system. As a result of the simulations developed, the pressure distribution is obtained in the contact area between the cartilage and synovial fluid (which is identified as interface). The synovial fluid velocity vector distribution is also presented in the fluid region as well as in the cartilage zone, the last one was modelled as a porous medium in the joint.

En este trabajo se desarrolló una simulación numérica para modelar una articulación sinovial, analizada de forma mecánica como un biorodamiento. En la literatura consultada se pudo observar que la mayoría de los modelos matemáticos encontrados en donde consideran articulaciones sinoviales plantean su análisis solamente en la región del líquido sinovial. Por ello, inicialmente se presenta la validación del modelo en la región del líquido sinovial que está en contacto con el biorodamiento, presentando una deformación proporcional al desplazamiento inducido. Posteriormente, la geometría utilizada para la validación del modelo numérico en el cual se plantean dos regiones correspondientes al líquido sinovial y cartílago articular, se basó en el estudio matemático propuesto por Jurczak , donde dicho modelo considera una deformación en la región del líquido sinovial y una porosidad de 0.2 para el cartílago articular. Adicionalmente a los resultados presentados, se propuso un nuevo modelo en donde se considera que la región de deformación se realiza en la zona del cartílago. Además se presentan resultados con un mayor rango de porosidad para el caso del cartílago con valores de 0.2, 0.5 y 0.8, así como diferentes valores de desplazamientos y velocidades, con la finalidad de representar diferentes movimientos o situaciones que pueden presentarse en una rodilla. El modelado numérico del sistema se realizó haciendo uso de la Dinámica de Fluidos Computacional (CFD por sus siglas en inglés) mediante el software Fluent®, en donde una de las herramientas importantes empleadas fue la de mallas dinámicas (dynamic meshes). Utilizando esta herramienta se logró inducir un desplazamiento en una de las paredes del sistema simulando el desplazamiento del fémur por carga y generar un remallado dinámico.
Facultad de Ingeniería Mecánica. Maestría Ciencias en Ingeniería Mecánica
Keywords: info:eu-repo/classification/cti/7; FIM-M-2013-1238; Biorodamiento; Validación; Deformación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5495